Liveness : performance in a mediatized culture - Auslander, Philip, 1956- (New York, NY : Routledge, 2023)
"Liveness: Performance in a Mediatized Culture addresses what may be the single most important question facing all kinds of performance today. What is the status of live performance in a culture dominated by mass media and digital technologies? Since its first appearance, Philip Auslander's ground-breaking book has helped to reconfigure a new area of study. Looking at specific instances of live performance such as theatre, music, sport, and courtroom testimony, Liveness offers penetrating insights into media culture, suggesting that media technology has encroached on live events to the point where many are hardly live at all. In this new edition, the author thoroughly updates his provocative argument to take into account the impact of the internet, and cultural, social, and legal developments. He also addresses the situation of live performance during the Covid-19 pandemic. In tackling some of the last great shibboleths surrounding the high cultural status of the live event, this classic book will continue to shape opinion and to provoke lively debate on a crucial artistic dilemma: what is live performance and what can it mean to us now? This is extensively revised, new edition of Liveness is an essential read for all students and scholars of performance-based courses"--
Keywords: Performing arts -- Performance; Music -- Performance; Trials; PERFORMING ARTS / Theater / History & Criticism; PERFORMING ARTS / Film & Video / History & Criticism; PERFORMING ARTS / Television / History & Criticism